Trichel pulse characteristics and mechanism of negative corona discharge in sub-millimeter gaps - Sun, Zhi (2023)
A negative corona discharge system of a needle-plate electrode suitable for sub-millimeter gaps is established to investigate Trichel pulse characteristics of negative corona discharge, in which an optical acquisition system is especially applied to timely observe a discharging corona. Electrostatics-hydrodynamics coupling simulations of air discharging in 100 μm-gaped needle-plate electrodes are performed to elucidate the micro-physical process of negative corona discharge. The impact ionization coefficient used for simulations and the experimentally recorded images of discharge corona are combined to characterize the active region of secondary electron emission. Dynamical distribution and transport of the charged particles are analyzed from multiphysics simulations to explain the microscopic mechanism for various stages of Trichel pulses. Even though the corona front near the plate electrode maintains a high rate of collision ionization and secondary electron excitation, the needle tip corona has not reached the threshold electric field of electron avalanche required for glow discharge, as manifested by discharge sawtooth waves comprised of corona and glow components. The amplitude and frequency of Trichel pulses increase, respectively, with impact ionization and secondary electron emission, which is evidently dependent on attachment coefficient and anion mobility. A higher attachment coefficient will lead to a significant reduction in amplitude of Trichel pulses. The present study provides a theoretical basis and experimental verification for micrometer discharges, which is the key point of insulation protections in microelectromechanical systems.